Economic Structure, Development Policy and Environmental Quality : An Empirical Analysis of Environmental Kuznets Curves with Chinese Municipal Data - He, Jie; Wang, Hua (2012)
In many cases, the relationship between environmental pollution and economic development can be generally depicted by an inverted U-shaped curve, or an environmental Kuznets curve, where pollution increases with income at the beginning and decreases after a certain level of income. However, what determine the shape of an enviornmental Kuznets curve, such as the height and the turning point of the curve, have not been thoroughly studied. A good understanding of the determinants is vitally important to the development community, especially for the developing world, where income growth is a high priority and yet environmental pollution also needs to be carefully controlled. This study analyzes the impacts of economic structure, development strategy and environmental regulation on the shape of the environmental Kuznets curve with a city-level panel dataset obtained from China. The results show that economic structure, development strategy and environmental regulation can all have important implications on the relationship between environmental environmental quality and economic development but the impacts can be different at different development stages.